A Sectoral Study of Part-Time Workers Covered by Collective Agreements: Why do Employers Hire Them? - Zeytinoglu, Isik (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1991)
This exploratory study examines, on a sectoral basis, employers' reasons for hiring part-time workers covered by collective agreements. The data for the study were collected from a survey of employers in Ontario. The results revealed that in the health care, education and retail trade sectors flexibility in scheduling work was considered as the most important reason for hiring part-time workers, but in the hospitality sector, the unavailability of full-time labour was the most important reason. While the health care and education sectors considered employees' preference for part-time work also as relatively important, the hospitality and retail trade sectors placed more emphasis upon flexibility in employment décisions andsavings in wages and benefits.